Quantum oscillatory interaction between isovalent centers in semiconductors. (1st March 2022) - Bao, Kejie; Zhang, Xiaodong; Chen, Hang; Zhu, Junyi
Abstract: Interaction between isovalent centers is of great interest in device physics. We discovered a quantum oscillatory interaction based on the first principles calculations of two identical isovalent centers in C/Ge/Sn co-doped Si. The interaction is explained by Green's function's analysis and the linear combination of atomic orbitals (LCAO) method. One point defect interacts with another by a product between the defect potentials and the summation term that characterizes the metallization process of the host lattice. The trend of the oscillation is an intrinsic property of the host. The interaction mechanism is further verified by the calculations of the isovalent pairs with different elements. Our works shed light on the precise control of defects in semiconductors.